Reporting System Within The Framework Of International Human Rights Conventions (Damascus University Journal for legal sciences, 2024)
The system of receiving and examining reports is one of the most accepted procedures by states and is applied at the international level. This system has been stipulated in all international human rights conventions concluded within the framework of the United Nations. The reports that are submitted are divided into preliminary, periodic and supplementary. Plus shadow reports. Reporting aims to regularly supervise the implementation of human rights conventions, and it is not based primarily on antagonism, but rather on the method of dialogue. Reporting is not something that is imposed on a state that is unwilling to do so, nor is it a contested process, but rather is based on the assumption that a degree of international accountability of a routine nature to comply with is in the interest of the state itself, its citizens and the international community.
Keywords: Human Rights Conventions; Reporting System; Convention Committees.